In silico analysis of AHJD‐like viruses, Staphylococcus aureus phages S24‐1 and S13′, and study of phage S24‐1 adsorption. Issue 2 (4th March 2014) - Uchiyama, Jumpei; Takemura‐Uchiyama, Iyo; Kato, Shin‐ichiro; Sato, Miho; Ujihara, Takako; Matsui, Hidehito; Hanaki, Hideaki; Daibata, Masanori; Matsuzaki, Shigenobu
Abstract Staphylococcus aureus is a clinically important bacterium that is commensal in both humans and animals. Bacteriophage (phage) attachment to the host bacterial surface is an important process during phage infection, which involves interactions between phage receptor‐binding proteins and host receptor molecules. However, little information is available on the receptor‐binding protein of S. aureus phages. S. aureus virulent phages S24‐1 and S13′ (family Podoviridae, genus AHJD‐like viruses) were isolated from sewage. In the present study, we investigated the receptor‐binding protein of AHJD‐like viruses using phage S24‐1. First, based on a comparative genomic analysis of phages S24‐1 and S13′, open reading frame 16 (ORF16) of phage S24‐1 was speculated to be the receptor‐binding protein, which possibly determines the host range. Second, we demonstrated that this was the receptor‐binding protein of phage S24‐1. Third, our study suggested that wall teichoic acids in the cell walls of S. aureus are the main receptor molecules for ORF16 and phage S24‐1. Finally, the C‐terminal region of ORF16 may be essential for binding to S. aureus. These results strongly suggest that ORF16 of phage S24‐1 and its homologs may be the receptor‐binding proteins of AHJD‐like viruses.